Determinan Perilaku CERDIK sebagai Upaya Pencegahan Dini Penyakit Tidak Menular pada Mahasiswa Universitas Hang Tuah Pekanbaru - Rahma, Aisah Nadiatul; Lita, Lita; Purba, Christine Vita Gloria (Jurnal Kesehatan Komunitas, 2025)
CERDIK behavior is the behavior of preventing non-communicable diseases. According to the initial data survey of students who have non-communicable diseases at Hang Tuah University, Pekanbaru, as many as 17 students, including hypertension, diabetes mellitus, and asthma. The purpose of this study was to determine the factors associated with CERDIK behavior with knowledge, attitudes, sources of information, social support (family and peers) in Hang Tuah University students in Pekanbaru. This research method is quantitative analytic with cross sectional research design with proportional random sampling technique. The population of this study was 2434 students. The sample of this research is 182 students. Measuring tool used is a questionnaire. Processing data using computerization. The analysis used was univariate and bivariate analysis with the chi square test. The results of this study show that the factors associated with CERDIK behavior have a P value <α 0.05, namely knowledge (p = 0.002, POR = 2.852), attitude (p = 0.000, POR = 16.060), sources of information (p = 0.017, POR = 2.603), and social support (family and peers) (p = 0.000, POR = 5.677). From these results it can be concluded that all of the four variables are related to CERDIK behavior (knowledge, attitudes, sources of information, and social support (family and peers) in Hang Tuah University students in Pekanbaru. The suggestion in this study is that students apply CERDIK behavior to prevent non-communicable diseases and to Hang Tuah University Pekanbaru to make early prevention programs for students to avoid non-communicable diseases.